Long term outcomes of early and late diagnosed congenital diaphragmatic hernia and pulmonary asymmetry (Annals of Medical Research, 2021)
None
Keywords: s: Diaphragmatic Hernia; Long Term; Lung Volumetry; Pulmonary Asymmetry; Modified Ventilatory Index.